Physical Frictions and Digital Banking Adoption - Choi, Hyun-Soo; Loh, Roger K. (Management Science, 2024)
The behavioral literature suggests that minor frictions can elicit desirable behavior without obvious coercion. Using closures of ATMs in a densely populated city as an instrument for small frictions to physical banking access, we find that customers affected by ATM closures increase their usage of the bank’s digital platform. Other spillover effects of this adoption of financial technology include increases in point-of-sale transactions, electronic funds transfers, automatic bill payments and savings, and a reduction in cash usage. Our results show that minor frictions can help overcome the status quo bias and facilitate significant behavior change. This paper was accepted by David Sraer, finance. Supplemental Material: Data and the online appendix are available at https://doi.org/10.1287/mnsc.2023.4972 .